2008 16th IEEE Symposium on High Performance Interconnects 2008
DOI: 10.1109/hoti.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

A High-Speed Optical Multi-Drop Bus for Computer Interconnections

Abstract: Buses have historically provided a flexible communications structure in computer systems. However, signal integrity constraints of high-speed electronics have made multi-drop electrical busses infeasible. Instead, we propose an optical data bus for computer interconnections. It has two sets of optical waveguides, one as a fan-out and the other as a fan-in, that are used to interconnect different modules attached to the bus. A master module transmits optical signals which are received by all the slave modules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Tan et al [26] demonstrated a 10 Gbit/s optical link with GaAs based technology to implement an optical multi-drop memory bus. Vantrease et al [29] proposed Corona, which used photonic links to provide high bandwidth to the DRAM.…”
Section: Related Workmentioning
confidence: 99%
“…Tan et al [26] demonstrated a 10 Gbit/s optical link with GaAs based technology to implement an optical multi-drop memory bus. Vantrease et al [29] proposed Corona, which used photonic links to provide high bandwidth to the DRAM.…”
Section: Related Workmentioning
confidence: 99%
“…Tan et al [6] demonstrated the feasibility of using an optical data bus for computer interconnections to avoid signal integrity issues inherent in using multi-drop electrical buses. Batten et al [7] described a custom opto-electrical crossbar network that connects DRAM modules to processors.…”
Section: Related Workmentioning
confidence: 99%